Gd3+ co-doping influence on the morphological, up-conversion luminescence and magnetic properties of LiYF4:Yb3+/Er3+ nanocrystals. (July 2019) - Secu, C.E.; Bartha, C.; Matei, E.; Negrila, C.; Crisan, A.; Secu, M.
Abstract: The influence of the Gd 3+ co-dopant on the structure, morphology and up-conversion luminescence/magnetic properties of the LiYF4 :Gd 3+ /Yb 3+ /Er 3+ nanocrystals was investigated and compared to those of Gd-free samples. Electron microscopy has indicated an inhibiting effect of the agglomeration and collapsing process of the nanocrystals compared to the Gd-free powder samples. The surface analysis of nanocrystals have not shown oxygen-metal bonds related to the metal oxidation within the surface nanometric layer. The paramagnetic properties are related to the magnetic moment of the Gd 3+ ions. The up-conversion luminescence of the LiYF4 :Gd 3+ /Yb 3+ /Er 3+ nanocrystals is about six times stronger than in LiYF4 :Yb 3+ /Er 3+ nanocrystals; the enhancement effect is most probably due to the lattice distortion induced by the Gd co-doping. Highlights: Gd-codoping of LiY(Gd)F4 :Yb/Er nanocrystals inhibited their agglomeration and collapsing process. There is no metal oxidation within the nanocrystals surface nanometric layer. The up-conversion luminescence enhancement was assigned to the lattice distortion that affects the crystal field and transition probabilities. The paramagnetic properties are related to the magnetic moment of the Gd 3+ ions.